Characteristics of Contact Dermatitis Patients (Irritant and Allergic) in RSUD Batara Siang Pangkep District - Aidah Nurul Faizah; Nurelly N. Waspodo; Arina Fathiyyah Arifin; Hermiaty Nasruddin; Lisa Yuniati (Media Publikasi Promosi Kesehatan Indonesia (MPPKI), 2024)
Introduction: Contact dermatitis is the occurrence of an inflammation of the skin caused by exposure to a toxin (primary irritant) or by an allergenic material (sensitizer) or by both. At the 2009 meeting of Dermatologists, it was stated that 90% of occupational skin diseases are contact dermatitis, both irritant and allergic. 92.5% of occupational skin diseases are contact dermatitis, 5.4% due to skin infections 2.1% of skin diseases due to other causes. Objective: To study the characteristics of contact dermatitis (irritant and allergic) at Batara Siang Regional General Hospital, Pangkep Regency, South Sulawesi Province in 2022-2023. Methods: This research is quantitative research with descriptive research design. The sampling method is total sampling and as for the samples obtained from medical record data, namely 268 cases of contact dermatitis at Batara Siang Regional General Hospital, Pangkep Regency. Results: The number of contact dermatitis cases was 268 cases consisting of 209 cases of ACD and 59 cases of ICD. Based on gender, the most cases were female in ACD and ICD, namely 41 ACD patients and 17 ICD patients in 2022, 79 ACD patients and 20 ICD patients in 2023. Based on age, 45-64 years old is the most common in ACD and ICD, namely 25 ACD patients and 9 ICD patients in 2022, 47 ACD patients and 11 ICD patients in 2023. Based on occupation, ACD is most common in students, namely 17 patients in 2022 and 32 patients in 2023 and in ICD, the work of housewives is 9 patients in 2022 and 10 patients in 2023. Based on the history of atopy, most of them did not have a history of atopy in both ACD and ICD, namely 69 ACD patients and 25 ICD patients in 2022, 128 ACD patients and 30 ICD patients in 2023. Conclusion: Most characteristics based on gender, age, occupation and atopic history of ACD and ICD in 2022 and 2023 are mostly similar.